Identification of Novel Phytase Genes from an Agricultural Soil-Derived Metagenome - Tan, H.; Mooij, M.; Barret, M.; Hegarty, P.; Harrington, C.; Dobson, A.; O'Gara, Fergal (The Korean Society for Microbiology, 2014)
Environmental microorganisms are emerging as an important source of new enzymes for wide-scale industrial application. In this study, novel phytase genes were identified from a soil microbial community. For this, a function-based screening approach was utilized for the identification of phytase activity in a metagenomic library derived from an agricultural soil. Two novel phytases were identified. Interestingly, one of these phytases is an unusual histidine acid phosphatase family phytase, as the conserved motif of the active site of PhyX possesses an additional amino acid residue. The second phytase belongs to a new type, which is encoded by multiple open reading frames (ORFs) and is different to all phytases known to date, which are encoded by a single ORF.